East Asian Arabis species (Brassicaceae) exemplify past hybridization and subsequent emergence of three main evolutionary lineages in East Asia, America and the amphi-Beringian region - Koch, Marcus; Grosser, Jan (Botanical journal of the Linnean Society, 2017)
Phylogenetic relationships and the evolutionary history of East Asian Arabis spp. (Brassicaceae) were investigated using plastid trnL-F and nuclear internal transcribed spacer 1 and 2 sequences (ITS). This study tested the widespread assumption of the occurrence of Arabis hirsuta in East Asia and, in particular, in China. We were able to show that this is not the case. East Asian and North American Arabis are represented by three evolutionary lineages that arose via reticulate evolution among taxa, which are more closely related to A. planisiliqua subsp. nemorensis and A. ciliata. Early divergence of these three lineages is placed in the Pliocene, mostly probably in East Asia. In Arabideae, the A. planisiliqua subsp. nemorensis lineage probably served as one parental source; however, this species shows, at present, a wide Eurasian distribution, but it does not reach East Asia and the amphi-Beringian region. The second parental source was difficult to define, because respective sister species are no longer present in East Asia and all close relatives are distributed in Europe and Asia Minor only. In all three evolutionary lineages amphi-Beringian distribution and differentiation patterns date back to the Pleistocene. However, all three lineages have had secondary contact and additional reticulate evolutionary patterns among them are demonstrated.